Immuno-reactivity of recombinant non-structural protein 3 N-terminus (rNS3Nt) in indirect-ELISA for detection of bluetongue viral antibodies in serum samples - CHACKO, N; BISWAS, S K; MOHANTY, N N; CHAND, K; MONDAL, B; PANDEY, A B; SHIVACHANDRA, S B (The Indian Journal of Animal Sciences, 2017)
Bluetongue, an arthropod borne non-contagious disease of ruminants especially sheep, is caused by bluetongue virus (BTV). Detection of BTV antibodies in susceptible hosts is considered to be of significance in disease diagnosis and differentiation. In the present study, a partial NS3 gene encoding for non-structural protein-3 N-terminus (1MT117 aa) of BTV-23, produced as purified recombinant NS3Nt fusion protein ( 32 kDa) using prokaryotic expression system (Escherichia coli), was evaluated as a candidate antigen in an indirect-ELISA (rNS3Nt-ELISA) to measure the serologic response to NS3 protein in small ruminants. The rNS3Nt fusion protein obtained in sufficient quantity and quality has good reactivity in detecting NS3 specific antibodies in field serum samples by indirect-ELISA. As NS3 protein is highly conserved, rNS3Nt-ELISA has potential for NS3 specific detection of antibodies in BTV affected animals irrespective of different viral serotypes. In comparison to structural protein (VP7) based c-ELISA kit and i-ELISA kit, the diagnostic sensitivity (85.1%, 86.2%) and specificity (92.5%, 93.2%) of rNS3Nt-ELISA were found to be relatively lower, respectively. Nevertheless, the study indicated the potential utility of rNS3Nt-ELISA as an alternate assay in routine sero-diagnosis of BTV infection and possible sero-surveillance of ruminants under DIVA strategy.